Las estrategias metodológicas que utiliza la maestra parvularia y su incidencia en el aprendizaje en los niños y niñas del primer grado de educación general básica del centro educativo fiscal Manuelita Miller, ciudad de Quito. Periodo Lectivo 2014-2015. Lineamientos alternativos - Saraguro Veintimilla, Mercy Maritza (2014)
This thesis is descriptive, analytical scientist named character: "METHODOLOGICAL STRATEGIES USED BY THE NURSERY TEACHER AND ITS IMPACT ON BASIC GENERAL EDUCATION FIRST YEAR CHILDREN LEARNING "MANUELITA MILLER" SCHOOL QUITO CITY. PERIOD 2014-2015 ". ALTERNATIVE GUIDELINES. It was structure and developed according to the rules of the Current Academic System at the Loja National University. The general objective of this: was establish the incidence of methodological strategies in the children’s learning on basic general education first year children learning. The methods used for the preparation of this research work were: scientific, analytic-synthetic, inductive, deductive, descriptive statistical model. The techniques and instruments used were: Survey applied to teachers of children in the first year of primary school education "Manuelita Miller" of the city of Quito, to identify the strategies used in their pre-school teacher workday and on observation guide applicate on basic general education first year children learning to improve the methodological strategies used by the nursery teacher. 75% of children has a favorable performance in the different discipline to the knowledge of the skills and the attitudes required for this leg of the boy while 25% needs to strength or alternate the strategies used by the teacher nursery to improve his chances of working and studying. 100% of teachers surveyed indicated that the methodological strategies used with children in the first year of basic education are not correct for the non-innovate and lack of knowledge of new strategies suggest the teacher to follow the same method learned traditionalist.